The Role of Environmental Law in Ensuring Sustainable Land Rights - WIDYATAMA, Pandu Rudy; IRNAWATI (Indonesia Strategic Sustainability, 2024)
The application of environmental laws has a strategic role in ensuring sustainable land rights, especially amid increasing pressure on land resources due to urbanization, industrialization, and climate change. This study aims to analyze the role of environmental law in ensuring the sustainability of land management with a literature study approach. The method used involves a review of legal documents, national and international regulations, as well as relevant previous research results. The findings suggest that environmental law serves as a regulatory framework for regulating land use, protecting ecosystems, and preventing overexploitation. However, inconsistent implementation, overlapping regulations, and weak law enforcement are the main obstacles to ensuring sustainability. The analysis also shows the importance of integrating environmental law and land law to overcome land conflicts and ensure equitable access to land, especially for vulnerable communities. In conclusion, strengthening environmental law through regulatory harmonization, institutional capacity building, and wider public participation is needed to realize sustainable land rights. This research provides a theoretical basis for the development of more comprehensive policies in managing land resources in a sustainable manner.